Consumption of Dates as an Accompaniment to Iron Tablets for Female Students with Anemia at MAN Purbalingga: Konsumsi Buah Kurma Sebagai Pendamping Tablet Tambah Darah Pada Siswi dengan Anemia di MAN Purbalingga - La’ali, Shaimaa Alma; Dewi, Pramesti; Safitri, Maya (Mattawang: Jurnal Pengabdian Masyarakat, 2025)
Anemia in adolescent girls and continues into adulthood will complicate pregnancy and childbirth later on. During the pre-survey at MAN Purbalingga, it was suspected that the female students were non-compliant in consuming iron tablets due to side effects such as nausea and a fishy smell, hence the need for non-pharmacological efforts to accompany the iron tablets. The purpose of this activity is to educate about the benefits of dates and provide dates as a companion iron supplements. This activity is conducted in three meetings. The first meeting was an anemia screening, the second meeting included pre and post-tests knowledge, education, and the provision of dates to be consumed for 7 days. The third meeting is a follow-up hemoglobin examination. The result is that out of 26 students in the anemia category, 18 students (69%) improved, 6 students (23%) remained the same, and 2 students (8%) worsened. The pre-test knowledge score of 68.85 increased to 96.15 in the post-test. The conclusion is that there was an increase in knowledge and the category of anemia. However, some still have anemia; on average, they have a history of typhoid fever, and the anemia worsens because they do not consume dates or iron tablets.